Importance of livestock sector highlighted in the final communique of the 15th Comprehensive Africa Agriculture Development Programme Partnership Platform Meeting in Nairobi, Kenya - CGIAR Research Program on Livestock (2019)
The Comprehensive Africa Agriculture Development Programme (CAADP) is a policy framework for agricultural transformation, wealth creation, food security and economic growth. To ensure inclusion of the livestock sector in discussions, the International Livestock Research Institute (ILRI) and the African Union Commission (AUC) hosted a session at the CAADP 2019 Partnership Meeting. Its success is reflected in the final meeting communiqué, which calls on the AUC and its partners to incorporate livestock and fisheries indicators in the Malabo Review Reporting mechanism.